Effect of Vitamin D supplementation in under-5 children with pneumonia: A randomized controlled trial - Jingi, Jagadish Krishna; Patil, Shailesh Shivajirao; Desai, Arunkumar (Indian Journal of Child Health, 2018)
Objective: The objective of the study was to study whether Vitamin D supplementation in under-5 children presenting with pneumonia and severe pneumonia reduces its duration and recurrences. Study Design: This study was designed as a double-blind, randomized, placebo-controlled trial. Setting: Pediatric unit of a teaching institute. Methods: A total of 80 children aged between 2 months and 5 years with the diagnosis of pneumonia and severe pneumonia (as per the WHO definition) admitted over a period of 1 year were included in the study. Children with features of rickets, severe malnutrition, asthma, any underlying medical disorders, and if received Vitamin D supplementation over the past 12 months were excluded from the study. Children were randomized into two groups. Intervention group received 300,000 IU (international units) of Vitamin D (1 ml), and the control group received 1 ml of sterile water as a placebo along with antibiotics and supportive care. Children were monitored for the resolution of symptoms. The two groups were comparable for baseline demographic, socioeconomic, clinical, and laboratory parameters. All the children were followed up for 3 months after discharge for any repeat episodes of pneumonia. Results: Time to resolution of symptoms (fever, tachypnea, and chest retractions) was not significant (3.63